Overlaps of Skeletal Muscle Fatigue and Skeletal Muscle Damage: The Muscle Injury Continuum - Carsten Schwiete; Christian Roth; Joachim Mester; Holger Broich; Michael Behringer (Sports Medicine - Open)
Abstract Background Muscle fatigue has long been identified as a potential risk factor for muscle overuse injuries, frequently occurring due to rapid eccentric contractions. Traditionally, muscle fatigue was thought to arise mainly to metabolic stress, whereas muscle damage was considered a consequence of mechanical overload. However, this binary approach fails to capture the complex physiological mechanisms, including prolonged-force depression, enzyme leakage or inflammatory responses, which overlap between both entities. Main Text This narrative review synthesizes evidence regarding physiological and mechanical overlaps between muscle fatigue and muscle damage. It elaborates on the concept of a muscle injury continuum, including forms of muscle fatigue, possibly leading to mechanical tissue damage, and potentially culminating in severe muscle injuries. Additionally, the relevance of the overlaps for load monitoring and injury prevention in professional sports are discussed. Conclusion Understanding and recognizing the interplay between muscle fatigue and muscle damage is crucial for developing individualized prevention strategies, minimizing injury risk, and enhancing performance. This comprehensive approach is vital for improving load management and ensuring the long-term health and efficiency of athletes.